MODEL STEM UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS V SEKOLAH DASAR - Damayanti , Alfina; Bayu Kelana, Jajang (LPPM Universitas Bina Bangsa, 2025)
This research aims to determine the increase in problem solving abilities in the water cycle material by applying the Science, Technology, Engineering and Mathematics (STEM) model. This research uses a pre-experimental design. The research methocd used is a quantitative method with One Group Pre-test and Post-test Design. The population in this study were fifth grade elementary school students, with a sample size of 30 students. The pre-test and post-test results were analyzed using the IBM Statistics program. To measure the increase in problem solving abilities, a normality test, paired sample t test and N-Gain test were carried out. The results of the normality test calculation obtained by the pre-test value obtained sig. (2 – tiled) 0.094 and post-test obtained sig. (2 – tiled) 0.133 > 0.05 then Ho is accepted. The results of the paired sample t test obtained a Sig value. (2-tailed) of 0.000 <0.05. Then it got an N-Gain value of 0,77 in the high category. From these results it can be concluded that the application of the Science, Technology, Engineering and Mathematics (STEM) model can improve the problem solving abilities of fifth grade elementary school students to have a good influence or impact on learning.